Hyper-Osmotic Stress Elicits Membrane Depolarization and Decreased Permeability in Halotolerant Marine Debaryomyces hansenii Strains and in Saccharomyces cerevisiae - Capusoni, Claudia; Arioli, Stefania; Donzella, Silvia; Guidi, Benedetta; Serra, Immacolata; Compagno, Concetta (Frontiers in Microbiology, 2019)
The use of seawater and marine microorganisms can represent a sustainable alternative to avoid large consumption of freshwater performing industrial bioprocesses. Debaryomyces hansenii, which is a known halotolerant yeast, possess metabolic traits appealing for developing such processes. For this purpose, we studied salt stress exposure of two D. hansenii strains isolated from marine fauna. We found that the presence of sea salts during the cultivation results in a slight decrease of biomass yields. Nevertheless, higher concentration of NaCl (2 M) negatively affects other growth parameters, like growth rate and glucose consumption rate. To maintain an isosmotic condition, the cells accumulate glycerol as compatible solute. Flow cytometry analysis revealed that the osmotic adaptation causes a reduced cellular permeability to dyes like SYBR Green I and SYTO™ 24. We demonstrate that this fast and reversible phenomenon is correlated to the induction of membrane depolarization, and occurred even in presence of high concentration of sorbitol. The decrease of membrane permeability induced by osmotic stress confers to D. hansenii resistance to cationic drugs like Hygromycin B. In addition, we describe that also in Saccharomyces cerevisiae the exposure to hyper-osmotic conditions induced membrane depolarization and reduced the membrane permeability. These aspects are very relevant for the optimization of industrial bioprocesses, as in the case of fermentations and bioconversions carried out by using media/buffers containing high nutrients/salts concentrations. Indeed, an efficient transport of molecules (nutrients, substrates and products) is the prerequisite for an efficient cellular performance, and ultimately for the efficiency of the industrial process.